Soft magnetic alloy powder, magnetic core, magnetic components, and electronic equipment
Patent Information
- Application Number
- JP2022138395
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-08-31
- Publication Date
- 2026-10-22
- Estimated Expiration
- 2042-08-31
Smart Images

Figure 0007939811000024 
Figure 0007939811000025 
Figure 0007939811000026
Abstract
Description
[Technical Field]
[0001] This invention relates to soft magnetic alloy powder, magnetic core, magnetic component, and electronic equipment. [Background technology]
[0002] Patent Document 1 describes a toroidal core containing amorphous soft magnetic powder. The amorphous soft magnetic powder is metallic glass and has an average Wadell sphericity of 0.90 or higher. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2011-023673 [Overview of the project] [Problems that the invention aims to solve]
[0004] An exemplary embodiment of the present invention aims to obtain a soft magnetic alloy powder and a magnetic core with improved DC superposition characteristics that can be used to fabricate a magnetic core with improved DC superposition characteristics. [Means for solving the problem]
[0005] To achieve the above objective, the soft magnetic alloy powder of an exemplary embodiment of the present invention is A soft magnetic alloy powder comprising: first particles consisting of soft magnetic alloy particles with a particle diameter of D50 or less; second particles consisting of soft magnetic alloy particles with a particle diameter greater than D50 and D60 or less; third particles consisting of soft magnetic alloy particles with a particle diameter greater than D60 and D70 or less; fourth particles consisting of soft magnetic alloy particles with a particle diameter greater than D70 and D80 or less; and fifth particles consisting of soft magnetic alloy particles with a particle diameter greater than D80 and D90 or less. Of the first to fifth particles, the average particle diameter of the nth particle is x n (μm), the average circularity of the nth particle is y n, the variance of the circularity of the n-th particle is z n as, points(x n ,y n )(n=1 to 5) are plotted on the xy plane, the slope my of the approximate straight line is -0.0030 or more, points(x n ,z n )(n=1 to 5) are plotted on the xz plane, the slope mz of the approximate straight line is 0.00050 or less.
[0006] To achieve the above object, a magnetic core according to an exemplary embodiment of the present invention comprising first particles made of soft magnetic alloy particles having a particle diameter of D50 or less, second particles made of soft magnetic alloy particles having a particle diameter greater than D50 and D60 or less, third particles made of soft magnetic alloy particles having a particle diameter greater than D60 and D70 or less, fourth particles made of soft magnetic alloy particles having a particle diameter greater than D70 and D80 or less, and fifth particles made of soft magnetic alloy particles having a particle diameter greater than D80 and D90 or less. Among the first to fifth particles, the average particle diameter of the n-th particle is X n (μm), the average circularity of the n-th particle is Y n , and the variance of the circularity of the n-th particle is Z n as, points(X n ,Y n )(n=1 to 5) are plotted on the XY plane, the slope mY of the approximate straight line is -0.0030 or more, points(X n ,Z n )(n=1 to 5) are plotted on the XZ plane, the slope mZ of the approximate straight line is 0.00050 or less.
[0007] The magnetic core may further contain a resin.
[0008] A magnetic component according to an exemplary embodiment of the present invention includes the above magnetic core.
[0009] An electronic device according to an exemplary embodiment of the present invention includes the above magnetic core. [Brief Description of the Drawings]
[0010] [Figure 1] Figure 1 is a projection view of powder particles. [Figure 2] Figure 2 is a projection view of powder particles. [Figure 3] Figure 3 is a projection view of powder particles. [Figure 4] Figure 4 is a projection view of powder particles. [Figure 5] Figure 5 is a projection view of powder particles. [Figure 6] Figure 6 is a projection view of powder particles. [Figure 7] Figure 7 shows an example of a chart obtained by X-ray crystallography. [Figure 8] Figure 8 shows an example of a pattern obtained by profile fitting the chart in Figure 7. [Figure 9] Figure 9 is a schematic cross-sectional view of the magnetic core. [Figure 10] Figure 10 is a schematic cross-sectional view of the magnetic core. [Figure 11A] Figure 11A is a schematic cross-sectional view of an elliptical water flow atomizer according to an exemplary embodiment of the present invention. [Figure 11B] Figure 11B is a schematic diagram of the coolant flow in the elliptical water flow atomizer shown in Figure 11A, viewed from the vertical direction. [Figure 12A] Figure 12A is a schematic diagram showing the flow of cooling water in a conventional atomizing device, viewed from the side. [Figure 12B] Figure 12B is a schematic diagram of the cooling water flow shown in Figure 12A, viewed from the vertical direction. [Modes for carrying out the invention]
[0011] The following describes the soft magnetic alloy powder and magnetic core according to embodiments of the present invention.
[0012] The soft magnetic alloy powder according to this embodiment contains powder particles. When the powder particles contained in the soft magnetic alloy powder are classified into many types of powder particles according to differences in particle size, the average circularity is approximately the same for powder particles belonging to any classification, and the dispersion of circularity is approximately the same for powder particles belonging to any classification.
[0013] The soft magnetic alloy powder according to this embodiment is a soft magnetic alloy powder comprising: first particles consisting of soft magnetic alloy particles with a particle diameter of D50 or less; second particles consisting of soft magnetic alloy particles with a particle diameter greater than D50 and D60 or less; third particles consisting of soft magnetic alloy particles with a particle diameter greater than D60 and D70 or less; fourth particles consisting of soft magnetic alloy particles with a particle diameter greater than D70 and D80 or less; and fifth particles consisting of soft magnetic alloy particles with a particle diameter greater than D80 and D90 or less.
[0014] Then, among the first to fifth particles, the average particle diameter of the nth particle is x. n (μm), the average circularity of the nth particle is y n The dispersion of the circularity of the nth particle is z n Let point (x n ,y n When plotting (n=1~5) on the xy-plane, the slope my of the approximation line is -0.0030 or greater, and the point (x n ,z n When plotting (n=1~5) on the xz plane, the slope mz of the approximate line is 0.00050 or less.
[0015] `my` is preferably -0.0020 or greater. There is no specific upper limit for `my`, but for example, it should be 0.0000 or less.
[0016] mz is preferably 0.00030 or less. There is no particular lower limit for mz, but for example, it is 0.00005 or more.
[0017] The particle size of each powder particle is the equivalent diameter of its circular area. Hereafter, the equivalent diameter of the circular area may simply be referred to as the equivalent diameter of the circular area. It may also be called the Heywood diameter.
[0018] The circularity is calculated as 2 × (πS), where S is the area of the powder particle in the projected image and L is the perimeter of the powder particle. 1 / 2 It is expressed as / L. This degree of circularity is sometimes also called Wadell's degree of circularity.
[0019] The variance of circularity is the mean of the squares of the deviations from the mean of circularity.
[0020] D50 for soft magnetic alloy powder refers to the particle size at which the cumulative relative frequency based on the number of particles is 50% in the particle size distribution of the soft magnetic alloy powder. D60 for soft magnetic alloy powder refers to the particle size at which the cumulative relative frequency based on the number of particles is 60%. D70 for soft magnetic alloy powder refers to the particle size at which the cumulative relative frequency based on the number of particles is 70%. D80 for soft magnetic alloy powder refers to the particle size at which the cumulative relative frequency based on the number of particles is 80%. D90 for soft magnetic alloy powder refers to the particle size at which the cumulative relative frequency based on the number of particles is 90%.
[0021] In other words, the first particle is a powder particle whose cumulative relative frequency based on number is 50% or less in the particle size distribution of the soft magnetic alloy powder. The second particle is a powder particle whose cumulative relative frequency based on number is above 50% but 60% or less in the particle size distribution of the soft magnetic alloy powder. The third particle is a powder particle whose cumulative relative frequency based on number is above 60% but 70% or less in the particle size distribution of the soft magnetic alloy powder. The fourth particle is a powder particle whose cumulative relative frequency based on number is above 70% but 80% or less in the particle size distribution of the soft magnetic alloy powder. The fifth particle is a powder particle whose cumulative relative frequency based on number is above 80% but 90% or less in the particle size distribution of the soft magnetic alloy powder.
[0022] The approximate line is obtained by linearly approximating points plotted on a coordinate plane using the least squares method. Specifically, the slope of the line obtained from the approximation formula, i.e., the regression line, is calculated. The regression line represented on the xy plane shows the particle size dependence of the degree of circularity. The regression line represented on the xz plane shows the particle size dependence of the variation in circularity.
[0023] There are no particular restrictions on the average particle size D1 of the total powder particles contained in the soft magnetic alloy powder. However, from the viewpoint of making it easier to obtain soft magnetic alloy powder having the above configuration, it may be 1.0 μm or more and 25.0 μm or less, or 5.0 μm or more and 15.0 μm or less.
[0024] There are no particular restrictions on the average circularity C1 of the powder particles contained in the soft magnetic alloy powder, but from the viewpoint of making it easier to improve the DC superposition characteristics of the final magnetic core, it may be 0.90 or higher, or 0.95 or higher.
[0025] The following describes the methods for identifying the first to fifth particles in a soft magnetic alloy powder, and for calculating the average and variance of the circularity of each particle.
[0026] There are no particular restrictions on the method for identifying the first to fifth particles in soft magnetic alloy powder. First, the particle size distribution in the soft magnetic alloy powder is measured. There are no particular restrictions on the method for measuring the particle size distribution. It can be measured by various particle size analysis methods such as laser diffraction. In particular, it may be confirmed using a particle image analyzer called Morfologi G3 (Malvern Panalytic). Morfologi G3 is a device that disperses powder with air, projects the shape of individual particles, and can evaluate the resulting projection.
[0027] Specifically, the equivalent circular diameter (particle diameter) of each particle can be obtained from the projected area of each individual particle. In this embodiment, the equivalent circular diameter is the Heywood diameter. Then, the particle size distribution can be obtained from the equivalent circular diameter of each particle. From the obtained particle size distribution, the particle diameter when the cumulative relative frequency based on the number of particles is 50% can be defined as D50, when the cumulative relative frequency based on the number of particles is 60% as D60, when the cumulative relative frequency based on the number of particles is 70% as D70, when the cumulative relative frequency based on the number of particles is 80% as D80, and when the cumulative relative frequency based on the number of particles is 90% as D90. In this embodiment, the particle size distribution is measured from the equivalent circular diameters of at least 2000 particles, preferably 20000 particles or more.
[0028] Identify the first to fifth particles from the projection diagrams and particle size distributions of each individual particle. Of the first to fifth particles, determine the average particle diameter of the nth particle as x. n (μm), the average circularity of the nth particle is y n The dispersion of the circularity of the nth particle is z n Let point (x n ,y n When plotting (n=1~5) on the xy-plane, what is the slope my of the approximation line, and what is the slope my of the point (x n ,z n When plotting (n=1~5) on the xz plane, the slope mz of the approximate line can be calculated.
[0029] The Morphologi G3 can create and evaluate projection diagrams of numerous particles simultaneously, allowing for the rapid evaluation of the shapes of many particles. Therefore, it is suitable for evaluating particle size distribution and other parameters of soft magnetic alloy powder before molding. It can create projection diagrams for numerous particles, automatically calculate the particle diameter and circularity of individual particles, and then calculate the aforementioned parameters.
[0030] The projection diagrams for each particle size of sample number 7, an example described later, are shown in Figures 1 to 3. The projection diagrams for each particle size of sample number 1, a comparative example described later, are shown in Figures 4 to 6. Comparing Figures 1 to 3 with Figures 4 to 6, the soft magnetic alloy powder shown in Figures 1 to 3 shows less particle size dependence of the variation in circularity compared to the soft magnetic alloy powder shown in Figures 4 to 6.
[0031] It is difficult to produce the soft magnetic alloy powder according to this embodiment using conventional atomizing equipment. However, by using a specific atomizing equipment described later and appropriately controlling the manufacturing conditions, the soft magnetic alloy powder according to this embodiment can be produced.
[0032] There are no particular restrictions on the composition of the soft magnetic alloy powder according to this embodiment. For example, it may have an alloy composition of a crystal system such as Fe-Si, Fe-Co-Si, Fe-Co-Si-Cr, Fe-Ni, Fe-Ni-Mo, Fe-Si-Cr, Fe-Si-Al, Fe-Si-Al-Ni, or Fe-Ni-Si-Co.
[0033] From the viewpoint of reducing the coercivity of the soft magnetic alloy powder and thereby reducing the coercivity of the magnetic core made using the soft magnetic alloy powder, the alloy composition may be Fe-based amorphous or Fe-based nanocrystalline. Examples of Fe-based amorphous or Fe-based nanocrystalline alloy compositions include Fe-Nb-BPS, Fe-Co-Nb-BPS, Fe-Nb-B-Si-Cu, Fe-Nb-B, Fe-Si-B, Fe-Si-Cr-BC, Fe-Co-Si-Cr-BP, Fe-Co-Si-Cr-BPC, and Fe-Si-BC systems.
[0034] There are no particular restrictions on the microstructure of the soft magnetic alloy powder according to this embodiment. It may be an amorphous structure, a nanocrystalline structure, or a crystalline structure.
[0035] An amorphous structure refers to a structure in which the amorphousity rate X is 85% or more. Structures containing crystals within the range where the amorphousity rate is 85% or more are included in amorphous structures. Amorphous structures include structures that are generally composed of amorphous material or heteroamorphous structures. A heteroamorphous structure is a structure in which crystals exist within an amorphous material. In the case of a heteroamorphous structure, the average crystal grain size of the crystals present in the amorphous material may be between 0.1 nm and 10 nm. A nanocrystalline structure is a structure in which the amorphousity rate X is less than 85% and the average crystal grain size of the crystals is 100 nm or less. In a nanocrystalline structure, the average crystal grain size of the crystals may be between 3 nm and 50 nm. A crystalline structure is a structure in which the amorphousity rate X is less than 85% and the average crystal grain size of the crystals is greater than 100 nm.
[0036] The amorphousness rate X can be measured by X-ray crystal structure analysis using XRD, or it may be measured by EBSD (electron beam scanning) or electron diffraction. The method of measurement using X-ray crystal structure analysis using XRD will be described below.
[0037] The amorphous fraction X of soft magnetic alloy powder is expressed by the following formula (1). X = 100 - (Ic / (Ic + Ia) × 100) ... (1) Ic: Crystalline scattering integrated intensity Ia: Amorphous scattering integral intensity
[0038] The amorphous fraction X is calculated by performing X-ray crystal structure analysis on soft magnetic alloy powder using XRD to identify the phases, reading the peaks of crystallized Fe or compounds (Ic: crystalline scattering integral intensity, Ia: amorphous scattering integral intensity), determining the crystallization fraction from the peak intensity, and calculating it using the above formula (1). The calculation method will be explained in more detail below.
[0039] soft magnetic alloy powderX-ray crystal structure analysis was performed using XRD to obtain the chart shown in Figure 7. Profile fitting was then performed using the Lorentz function of equation (2) below to obtain the crystal component pattern α showing the crystalline scattering integral intensity, as shown in Figure 8. c , amorphous component pattern α showing amorphous scattering integral intensity a , and the combined pattern α c+a The result is obtained. The amorphous fraction X is determined from the crystalline scattering integral intensity and amorphous scattering integral intensity of the obtained pattern using equation (1) above. The measurement range is the number of times when a halo originating from amorphous material can be confirmed. Occasionally The angle 2θ is set to a range of 30° to 60°. Within this range, the error between the integrated intensity measured by XRD and the integrated intensity calculated using the Lorentz function should be within 1%.
[0040]
number
[0041] By using the soft magnetic alloy powder according to this embodiment to fabricate a magnetic core, the DC superposition characteristics of the resulting magnetic core can be improved.
[0042] The magnetic core according to this embodiment contains the above-mentioned powder particles. When the powder particles contained in the magnetic core are divided into many types of particles based on differences in particle size in the cross-section of the magnetic core, the average circularity is approximately the same for particles belonging to any category, and the dispersion of circularity is approximately the same for particles belonging to any category.
[0043] The magnetic core according to this embodiment specifically comprises a soft magnetic alloy powder having: first particles made of soft magnetic alloy particles with a particle diameter of D50 or less; second particles made of soft magnetic alloy particles with a particle diameter greater than D50 and D60 or less; third particles made of soft magnetic alloy particles with a particle diameter greater than D60 and D70 or less; fourth particles made of soft magnetic alloy particles with a particle diameter greater than D70 and D80 or less; and fifth particles made of soft magnetic alloy particles with a particle diameter greater than D80 and D90 or less. Magnetic core fabricated using That is the case.
[0044] Then, among the first to fifth particles, the average particle diameter of the nth particle is X. n (μm), the average circularity of the nth particle is Y n The dispersion of the circularity of the nth particle is Z n As, point (X n ,Y n When plotting (n=1~5) on the XY plane, the slope mY of the approximation line is -0.0030 or greater, and point (X n ,Z n When plotting (n=1~5) on the XZ plane, the slope mZ of the approximate line is 0.00050 or less.
[0045] mY is preferably -0.0020 or greater. There is no particular upper limit to mY, but for example, it should be 0.0000 or less.
[0046] mZ is preferably 0.00030 or less. There is no particular lower limit for mZ, but for example, it is 0.00005 or more.
[0047] The regression line represented on the XY plane shows the particle size dependence of the degree of circularity. The regression line represented on the XZ plane shows the particle size dependence of the variation in circularity.
[0048] There are no particular restrictions on the average particle diameter D2 of the entire particle in the cross-section of the magnetic core, but from the viewpoint of making it easier to obtain a magnetic core having the above configuration, it may be 1.0 μm or more and 25.0 μm or less, or 5.0 μm or more and 15.0 μm or less.
[0049] There are no particular restrictions on the average circularity C2 of the entire particle in the cross-section of the magnetic core, but from the viewpoint of making it easier to improve the DC superposition characteristics of the magnetic core having the above configuration, it may be 0.70 or higher, 0.75 or higher, or 0.85 or higher.
[0050] The magnetic core may contain a resin in addition to the soft magnetic alloy particles described above. There are no particular restrictions on the type or content of the resin. Examples of resins include thermosetting resins such as phenolic resins and epoxy resins. The resin content may be 1% by mass or more and 5% by mass or less relative to the soft magnetic alloy.
[0051] The magnetic core according to this embodiment may contain other soft magnetic alloy particles, fine particles, non-magnetic particles, etc., that are distinguishable from the soft magnetic alloy particles described above, within a range in which the DC superposition characteristics are suitably maintained. There are no particular restrictions on the content of the other soft magnetic alloy particles, fine particles, and non-magnetic particles. For example, it may be 30 wt% or less of the total magnetic core. In addition, modifiers, preservatives, dispersants, etc. may be added to the magnetic core.
[0052] Next, we will explain the method for identifying the first to fifth particles in the soft magnetic alloy particles contained in the magnetic core, and the method for calculating the average and variance of the circularity of each particle.
[0053] First, the magnetic core is cut at an arbitrary point to obtain a cross-section. Next, the cross-section is observed. There are no particular restrictions on the method of observing the cross-section. For example, an electron microscope (SEM, STEM, TEM, etc.) may be used. There are no particular restrictions on the observation range or magnification; it is sufficient to observe the individual cross-sectional shapes of at least 2000 soft magnetic alloy particles.
[0054] Next, the equivalent circular diameter of each particle within the observation range is calculated. There are no particular restrictions on the method for calculating the equivalent circular diameter. For example, an analysis program may be used. However, when using an analysis program, there is a possibility that parts that are clearly not particles may be mistakenly identified as particles. Such parts should be excluded as appropriate.
[0055] Then, the particle size distribution can be obtained from the equivalent circle diameter of each individual particle. From the obtained particle size distribution, the particle size when the cumulative relative frequency based on the number of particles is 50% can be defined as D50, the particle size when the cumulative relative frequency based on the number of particles is 60% can be defined as D60, the particle size when the cumulative relative frequency based on the number of particles is 70% can be defined as D70, the particle size when the cumulative relative frequency based on the number of particles is 80% can be defined as D80, and the particle size when the cumulative relative frequency based on the number of particles is 90% can be defined as D90. In this embodiment, the particle size distribution is measured from the equivalent circle diameter of at least 2000 particles.
[0056] A schematic cross-sectional view of the magnetic core according to this embodiment is shown in Figure 9, and a schematic cross-sectional view of a conventional magnetic core is shown in Figure 10. Compared to the magnetic core shown in Figure 10, the magnetic core shown in Figure 9 exhibits less particle size dependence of variation in the circularity of the soft magnetic alloy particles.
[0057] The particle size distribution and circularity of the soft magnetic alloy powder, as confirmed by Morphologi G3, do not match the particle size distribution and circularity of the soft magnetic alloy particles in the cross-section of the final magnetic core, also based on particle number.
[0058] However, there is a correlation between the particle size distribution and circularity of the magnetic powder, as confirmed by Morphologi G3, and the particle size distribution and circularity of the magnetic powder particles in the cross-section of the final magnetic core, also based on particle number. Therefore, by confirming the particle size distribution and circularity of the soft magnetic alloy powder with Morphologi G3, it is possible to predict, to some extent, the particle size distribution of the soft magnetic alloy particles in the cross-section of the final magnetic core. In other words, it is easy to control the particle size distribution and circularity of the soft magnetic alloy particles in the cross-section of the final magnetic core, based on particle number, by controlling the particle size distribution and circularity of the soft magnetic alloy powder before molding.
[0059] A magnetic core produced by pressure molding the soft magnetic alloy powder according to this embodiment is likely to be a magnetic core according to this embodiment. Furthermore, by changing the molding pressure between the magnetic core according to this embodiment and a conventional magnetic core to make the relative permeability μ equivalent, a magnetic core with high DC superposition characteristics can be obtained. There are no particular restrictions on the relative permeability μ of the magnetic core.
[0060] The packing density of soft magnetic alloy particles in the magnetic core can be controlled by controlling manufacturing conditions such as molding pressure and the resin content. The packing density may be, for example, 70 vol% to 90 vol%.
[0061] In magnetic cores manufactured by pressure molding soft magnetic alloy powder, when measuring the circularity of soft magnetic alloy particles contained in the magnetic core according to particle size, larger particle sizes tend to result in smaller average circularity and larger dispersion of circularity. In other words, the particle size dependence of the magnitude of circularity and the particle size dependence of the dispersion of circularity tend to be larger. In particular, when soft magnetic alloy particles with large particle sizes and irregular shapes are included in the magnetic core, local saturation is likely to occur around them. As a result, the DC superposition characteristics tend to deteriorate particularly easily.
[0062] Conventionally, it has been difficult to reduce both the particle size dependence of the magnitude of circularity and the particle size dependence of the dispersion of circularity. However, the inventors have found that a soft magnetic alloy powder with low particle size dependence of both the magnitude of circularity and the dispersion of circularity can be produced using the atomization apparatus described later. Furthermore, the magnetic core produced using this soft magnetic alloy powder exhibits low particle size dependence of both the magnitude of circularity and the dispersion of circularity, resulting in improved DC superposition characteristics. It will be improved. The inventors have discovered this.
[0063] The method for producing the soft magnetic alloy powder according to this embodiment will be described below.
[0064] There are no particular limitations on the method for producing soft magnetic alloy powder. However, the inventors have found that when soft magnetic alloy powder is produced by gas atomization using the elliptical water flow atomization apparatus 10 described later, it is easier to obtain soft magnetic alloy powder in which both the particle size dependence of the circularity and the particle size dependence of the dispersion of circularity are small.
[0065] The following describes an example of a method for producing soft magnetic alloy powder. Soft magnetic alloy powder may be produced by gas atomization. Specifically, it may be produced using the elliptical water flow atomizer 10 shown in Figure 11A. The elliptical water flow atomizer 10 is a device that can generate an elliptical spiral cooling water flow, and by using this elliptical water flow atomizer 10, soft magnetic alloy powder can be produced under optimal rapid cooling conditions.
[0066] As shown in Figure 11A, the elliptical water flow atomizing device 10 includes a molten metal supply unit 60 and a cooling unit 30 located vertically below the supply unit. In Figure 11A, the vertical direction is the Z-axis direction. The molten metal supply unit 60 has a heat-resistant container 62 for containing molten metal 61, and a heating coil 64 is arranged around the outer circumference of the container 62. When manufacturing soft magnetic alloy powder, a master alloy having the desired alloy composition is placed in the container 62, the master alloy is melted by the heating coil 64, and the temperature of the resulting molten metal 61 is maintained within a predetermined range.
[0067] The method for manufacturing the master alloy is not particularly limited. For example, the master alloy can be obtained by weighing the raw materials (pure metals, etc.) of each element constituting the soft magnetic alloy powder to achieve the desired alloy composition, and then melting the raw materials by high-frequency heating in a chamber with a predetermined vacuum. Furthermore, the temperature of the molten metal 61 obtained by melting the master alloy is not particularly limited. The temperature of the molten metal 61 should be set considering the melting point of an alloy having the desired alloy composition. For example, it can be set to 1200°C to 1600°C.
[0068] A discharge port 63 is formed at the bottom of the container 62. The molten metal 61, which is maintained at a predetermined temperature, is discharged from the discharge port 63 as dripping molten metal 61a toward the inner circumferential surface 33 of the cylindrical body 32 that constitutes the cooling section 30.
[0069] Furthermore, a gas injection nozzle 66 is positioned on the outside of the outer bottom wall of the container 62, surrounding the discharge port 63. This gas injection nozzle 66 is equipped with an injection port 67, from which high-pressure gas is injected toward the dripping molten metal 61a. More specifically, the high-pressure gas is injected diagonally downward from the entire circumference of the molten metal 61 discharged from the discharge port 63. As a result, the dripping molten metal 61a becomes numerous droplets, which are carried toward the inner surface 33 of the upper inner side of the cylindrical body 32 along with the gas flow.
[0070] The high-pressure gas may be an inert gas such as nitrogen gas, argon gas, or helium gas, or a reducing gas such as ammonia decomposition gas.
[0071] To obtain the soft magnetic alloy powder according to this embodiment, the ratio of the flow rate (Gv) to the gas pressure (Gp) of the atomizing gas (high-pressure gas) is adjusted. A suitable Gv / Gp can vary depending on the composition of the master alloy, but for example, 0.5 m 3 / MPa or more 30m 3 It may be less than / MPa.
[0072] Furthermore, the average particle size D1 of the soft magnetic alloy powder can be controlled by the discharge flow rate of the molten metal 61. The lower the discharge flow rate, the smaller the average particle size D1 tends to be. The higher the discharge flow rate, the larger the average particle size D1 tends to be. In addition to the discharge flow rate, the average particle size D1 can also be controlled by adjusting factors such as the gas injection pressure, the distance the dropping molten metal 61a travels to reach the cooling section 30, and the water flow velocity in the cooling section 30.
[0073] The cooling unit 30 includes a cylindrical body 32 having an inner circumferential surface 33, a coolant outlet 36 provided at the upper part of the cylindrical body 32, and a discharge section 34 provided at the lower part of the cylindrical body 32. The cylindrical body 32 is installed so that its axis O is inclined at a predetermined angle θ2 with respect to the vertical direction (Z-axis direction). Furthermore, the upper part of the cylindrical body 32 is cut in a horizontal direction perpendicular to the Z-axis direction while inclined at the predetermined angle θ2, and the upper surface of the cylindrical body 32 has an elliptical opening. In addition, the inner circumferential surface 33 of the cylindrical body 32 has an elliptical cross-section inclined at an angle θ1 with respect to the axis O, as shown in Figure 11B, and this elliptical cross-section is continuously formed along the axis O.
[0074] The angle θ1 is expressed as θ1 = (90 degrees - θ2), and the elliptical cross-section mentioned above is the horizontal cross-section of the inner circumferential surface 33 (cylinder 32) perpendicular to the vertical direction. The major axis of the ellipse in the horizontal cross-section of the inner circumferential surface 33 may coincide with the direction in which the axis O of the cylinder 32 is inclined with respect to the Z axis (vertical line). In other words, the cylinder 32 may be constructed such that the major axis of the horizontal cross-section is contained in a plane that includes the axis O of the cylinder 32 and the Z axis intersecting that axis O.
[0075] As shown in Figure 11B, the minor axis of the ellipse in the horizontal cross-section of the inner circumferential surface 33 is defined as W1, and the major axis of the ellipse is defined as W2. To obtain the soft magnetic alloy powder according to this embodiment, the ratio of the major axis W2 to the minor axis W1 (W2 / W1) is adjusted. A suitable W2 / W1 can vary depending on the composition of the master alloy, but for example, it may be between 1.04 and 3.00.
[0076] The coolant outlet 36 in the cooling section 30 has a supply line 37 and a coolant discharge port 52. In the coolant outlet 36, the coolant supplied from the supply line 37 is discharged from the coolant discharge port 52 along the inner circumferential surface 33 of the cylindrical body 32. The coolant outlet 36 has an optimal structure for creating an elliptical spiral water flow. The coolant discharged from the coolant discharge port 52 flows downward from the axis O along the inner circumferential surface 33, drawing an elliptical spiral. The coolant discharged from the coolant discharge port 52 forms a coolant layer 50 with a constant thickness.
[0077] The molten metal 61a, which is injected toward the inner circumferential surface 33 by high-pressure gas, is rapidly cooled by the coolant layer 50 having an elliptical spiral water flow. In the elliptical spiral water flow generated in the coolant layer 50, the flow velocity is faster on the minor axis side of the ellipse and slower on the major axis side. Therefore, the molten metal 61a injected into the coolant layer 50 is carried downwards from the axis O by the elliptical spiral water flow, with its velocity changing in accordance with the coolant flow velocity. The injection point of the molten metal 61a may be the point where the curvature of the ellipse is minimized.
[0078] As described above, by changing the velocity of the dripping molten metal 61a flowing through the coolant layer 50, the vapor film generated around the dripping molten metal 61a is more easily detached from the dripping molten metal 61a. Therefore, the rapid cooling efficiency of the dripping molten metal 61a is improved. Then, the dripping molten metal 61a solidifies due to the elliptical spiral water flow in the coolant layer 50, yielding the soft magnetic alloy powder according to this embodiment. The soft magnetic alloy powder is discharged together with the coolant from the discharge section 34 located below the cylindrical body 32. The soft magnetic alloy powder removed from the elliptical water flow atomizer 10 may be subjected to appropriate treatments such as drying or classification.
[0079] The soft magnetic alloy powder according to this embodiment is produced using the above W2 / W1 and the above Gv / Gp These are thought to be contributing factors. W2 / W1 and Gv / Gp By suitably controlling this, the soft magnetic alloy powder according to this embodiment can be obtained. When W2 / W1 is small or Gv / Gp is large, the particle size dependence of the variation in circularity tends to increase. When W2 / W1 is large or Gv / Gp is small, the particle size dependence of the size of circularity tends to increase.
[0080] In contrast, in conventional atomizing devices, as shown in Figures 12A and 12B, the cross-section perpendicular to the axis O of the inner circumferential surface 33 of the cylindrical body 32 is circular (W2 / W1=1.00). Also, the coolant outlet 52 is circular in shape.
[0081] The particle size of the soft magnetic alloy powder may be adjusted by adjusting the particle size using dry classification or wet classification. Examples of dry classification methods include sieving classification using a dry sieve and airflow classification. Examples of wet classification methods include classification by wet filter filtration and classification by centrifugal separation.
[0082] An insulating coating may be formed on the soft magnetic alloy powder according to this embodiment. When forming an insulating coating on the surface of the soft magnetic alloy particles contained in the soft magnetic alloy powder, the soft magnetic alloy powder may be subjected to a coating-forming treatment such as heat treatment, phosphate treatment, mechanical alloying, silane coupling treatment, or hydrothermal synthesis.
[0083] The applications of the soft magnetic alloy powder according to this embodiment are not particularly limited. It can be applied to various magnetic components. In particular, the soft magnetic alloy powder can be suitably used as a material for magnetic cores in magnetic components such as inductors, transformers, and choke coils.
[0084] There are no particular limitations on the type of magnetic core according to this embodiment. The following describes the case where the magnetic core is a compacted magnetic core. That is, a method for obtaining a magnetic core by pressure molding will be described.
[0085] The method for manufacturing the magnetic core is not particularly limited. For example, first, a resin compound is obtained by kneading the soft magnetic alloy powder according to this embodiment with a resin. The resin compound may be granulated powder. At this time, soft magnetic alloy powder produced by a conventional gas atomizing apparatus, fine powder with an average particle size smaller than that of the soft magnetic alloy powder according to this embodiment, and / or non-magnetic powder may be added to the resin compound. Modifiers, preservatives, dispersants, etc. may also be added. Then, the resin compound is filled into a mold, pressure molded, and the resin is cured to obtain the magnetic core.
[0086] First, the soft magnetic alloy powder and the resin are mixed. Mixing in the resin makes it easier to obtain a molded body with high strength through molding. There are no particular restrictions on the type of resin. Examples include phenolic resin and epoxy resin. There are also no particular restrictions on the amount of resin added. When adding resin, it may be added in an amount of 1% to 5% by mass relative to the magnetic powder.
[0087] A mixture of soft magnetic alloy powder and resin is granulated to obtain granulated powder. There are no particular restrictions on the granulation method. For example, granulation may be carried out using a stirrer. There are no particular restrictions on the particle size of the granulated powder.
[0088] The resulting granulated powder is subjected to pressure molding to obtain a molded body. There are no particular restrictions on the molding pressure. For example, a surface pressure of 0.1 t / cm². 2 More than 20t / cm 2 The following is also possible: When using soft magnetic alloy powder produced using an elliptical water flow atomizing apparatus, the relative permeability μ can be increased with a smaller molding pressure compared to when using a conventional atomizing apparatus. Furthermore, a magnetic core with improved DC superposition characteristics can be obtained compared to when using a conventional atomizing apparatus.
[0089] Then, the resin contained in the molded body can be cured to obtain a magnetic core. There are no particular restrictions on the curing method, and heat treatment may be performed under conditions that can cure the resin used.
[0090] There are no particular restrictions on the application of the magnetic core. For example, it can be suitably used as a magnetic core for inductors, especially power inductors. Furthermore, it can also be suitably used in inductors in which the magnetic core and coil are integrally molded.
[0091] Furthermore, the magnetic cores and magnetic components using the above-mentioned magnetic cores can be suitably used in electronic devices.
[0092] In particular, the magnetic core described above tends to exhibit relatively high DC superposition characteristics, making it suitable for use in fields where miniaturization, high frequency, high efficiency, and energy saving are required. For example ,vinegarSmall, high-speed switching batteries used in smartphones and automotive equipment Source It can be suitably used in magnetic cores, magnetic components, and electronic devices. [Examples]
[0093] The present invention will be specifically described below based on examples.
[0094] (Experimental Example 1) <Soft magnetic alloy powder> The raw metals were weighed to obtain a soft magnetic alloy composition of 83.9Fe-12.2Nb-2.0B-1.8P-0.1S by weight ratio, and the master alloy was prepared by melting them using high-frequency heating. Specifically, pure metal raw materials such as Fe, Nb, and other minor components were prepared, and these pure metal raw materials were weighed so that the above soft magnetic alloy composition would be obtained after melting. The weighed pure metal raw materials were then melted using high-frequency heating in a vacuum chamber to obtain the master alloy.
[0095] The prepared master alloy was heated and melted to a molten state of 1500°C. Then, soft magnetic alloy powders with the alloy composition of each sample were produced by gas atomization. Specifically, when the molten master alloy was discharged from the discharge port towards the cooling section inside the cylinder, high-pressure gas was injected towards the discharged molten metal. N2 gas was used as the high-pressure gas. The molten metal collides with the cooling section (cooling water), cools and solidifies, and becomes soft magnetic alloy powder.
[0096] Sample No. 1, where the W2 / W1 ratio of the cylindrical body in the cooling section was 1.00, was atomized using the conventional atomizing apparatus shown in Figure 12. For the other samples where W2 / W1 > 1.00, the elliptical water flow atomizing apparatus shown in Figure 11 was used.
[0097] For the gas atomization method, the molten metal ejection rate was set to 1-20 kg / min, and the cooling water pressure to 1-30 MPa. Each of the above conditions was appropriately controlled to obtain the desired soft magnetic alloy powder. Furthermore, the parameter Gv / Gp, obtained by dividing the atomization gas flow rate Gv by the atomization gas pressure Gp, was set to the values shown in Table 1. Gv was approximately 4 m 3 ~16m 3 The values were varied within this range, and Gp was generally varied within the range of 0.5 MPa to 12 MPa.
[0098] Next, the obtained soft magnetic alloy powder was heat-treated to precipitate nanocrystals with a grain size of 30 nm or less, reducing the amorphousness rate X to 10%. Specifically, the heat treatment was performed at 400-650°C for 10-60 minutes.
[0099] For each sample, the composition of the master alloy and the composition of the powder were confirmed to be in general agreement by ICP analysis. Furthermore, X-ray diffraction measurements were performed on each powder to determine the amorphousness rate X. A structure consisting of amorphous material was considered to exist if the amorphousness rate X was 85% or higher. A structure consisting of nanocrystalline material was considered to exist if the amorphousness rate X was less than 85% and the average crystal grain size was 100 nm or less. A structure consisting of crystalline material was considered to exist if the amorphousness rate X was less than 85% and the average crystal grain size was greater than 100 nm. In Experimental Example 1, it was confirmed that all powders had a nanocrystalline structure.
[0100] Next, the average particle diameter D1 and average circularity C1 of each soft magnetic alloy powder were measured. First, individual particle projection images were observed using a Morphologi G3 (Malvern Panalytic). The shape of 20,000 powder particles was observed at a magnification of 10x. Specifically, 3cc of powder was dispersed at an air pressure of 1-3 bar, and projection images were taken using a laser microscope. The diameter equivalent to the circular area in the projection image of each powder particle was then measured as the particle diameter. The average particle diameter D1 was calculated by averaging the particle diameters of each powder particle based on the number of particles.
[0101] Furthermore, the circularity of individual powder particles was measured from the projection images of each particle. Then, the average circularity C1 of each powder particle was calculated based on the number of particles.
[0102] Furthermore, my and mz were calculated from the particle size and circularity of each powder particle.
[0103] <Magnetic core> Toroidal cores were fabricated using the soft magnetic alloy powders of each sample.
[0104] First, a resin compound was obtained by kneading soft magnetic alloy powder and epoxy resin. The mixing ratio of soft magnetic alloy powder to epoxy resin was controlled so that the resin content in the toroidal core was 2.5 wt%.
[0105] A toroidal molded body was obtained by filling a mold with a resin compound and applying pressure. The molding pressure was controlled so that the relative permeability μ (relative permeability without an applied DC magnetic field) of the final toroidal core was 30.
[0106] A toroidal core was obtained by heat-treating a toroidal molded body at 180°C for 60 minutes to cure the epoxy resin inside the molded body. The toroidal core had an outer diameter of 11 mm, an inner diameter of 6.5 mm, and a thickness of 2.5 mm. The required number of toroidal cores for the tests described later were manufactured.
[0107] The average particle diameter D2 and average circularity C2 of soft magnetic alloy particles in the cross-section of a toroidal core were measured. First, the toroidal core was cut at an arbitrary cross-section. Next, the soft magnetic alloy particles in the cross-section were measured at a magnification (100-1000) where they could be distinguished. double SEM images were observed. D2 and C2 were measured by analyzing the SEM images. Mac-View (Mountec Co., Ltd.) was used as the image analysis software. The particle diameter was measured from the shape of each particle in the SEM image, using the equivalent diameter of the circular area as the particle diameter. The average particle diameter D2 was calculated by averaging the particle diameters of each particle based on the number of particles.
[0108] Furthermore, the circularity of each particle was measured from the shape of each particle in the SEM image. Then, the average circularity C2 of each particle was calculated based on the number of particles.
[0109] Furthermore, the above mY and mZ values were calculated from the particle size and circularity of each particle.
[0110] The relative permeability μ of the toroidal core of each sample was confirmed to be 30 by the following method. First, polyurethane copper wire (UEW wire) was wound around the toroidal core. Then, without applying a DC current, the inductance of the toroidal core at a frequency of 1 MHz was measured using an LCR meter (Agilent Technologies 4284A), and the relative permeability μ was calculated from the obtained inductance. The relative permeability μ was then confirmed to be 30.
[0111] Furthermore, a DC magnetic field of 8 kA / m was applied to the toroidal core of each sample to measure its inductance, and the DC permeability μHdc was calculated from the obtained inductance. The increase rate of μHdc was calculated using the DC permeability μHdc of a toroidal core manufactured using a conventional atomizing apparatus (sample number 1 in Experimental Example 1) as a reference. A μHdc increase rate of 1.30 times or more was considered to indicate good DC superposition characteristics. A μHdc increase rate of 1.70 times or more was considered to indicate even better DC superposition characteristics, and a μHdc increase rate of 2.00 times or more was considered to indicate particularly good DC superposition characteristics. The results of the above tests are shown in Table 1.
[0112] [Table 1]
[0113] Table 1 shows that W2 / W1 is between 1.04 and 3.00, and Gv / Gp is 1m 3 / MPa or more 30m 3 When the pressure was below / MPa, the my and mz values of the soft magnetic alloy powder fell within the specified range. Furthermore, the mY and mZ values of the magnetic core (toroidal core) made using the said soft magnetic alloy powder fell within the specified range, and the DC superposition characteristics were good.
[0114] Conversely, when W2 / W1 was too small and Gv / Gp was too large, the absolute value of mz of the soft magnetic alloy powder became too large. As a result, the mZ of the magnetic core (toroidal core) made using the soft magnetic alloy powder fell outside the predetermined range, and the DC superposition characteristics deteriorated.
[0115] When W2 / W1 was too large and Gv / Gp was too small, the absolute value of my of the soft magnetic alloy powder became too large. As a result, the mY of the magnetic core (toroidal core) made using the soft magnetic alloy powder fell outside the predetermined range, and the DC superposition characteristics deteriorated.
[0116] (Experimental Example 2) The experiment was conducted under the same conditions as in Experiment 1, except that the composition of the soft magnetic alloy powder was changed by weight ratio to 67.1Fe-16.8Co-12.2Nb-2.0B-1.8P-0.1S (Table 2), 83.4Fe-5.6Nb-2.0B-7.7Si-1.3Cu (Table 3), and 86.2Fe-12.0Nb-1.8B (Table 4). In Experiment 2, it was confirmed that all the powders consisted of nanocrystals.
[0117] [Table 2]
[0118] [Table 3]
[0119] [Table 4]
[0120] Tables 2 to 4 show that when W2 / W1 and Gv / Gp were suitably controlled, the my and mz values of the soft magnetic alloy powder fell within the predetermined range. Furthermore, the mY and mZ values of the magnetic core (toroidal core) fabricated using the said soft magnetic alloy powder fell within the predetermined range, resulting in good DC superposition characteristics.
[0121] Conversely, when W2 / W1 was too small and Gv / Gp was too large, the absolute value of mz of the soft magnetic alloy powder became too large. As a result, the mZ of the magnetic core (toroidal core) made using the soft magnetic alloy powder fell outside the predetermined range, and the DC superposition characteristics deteriorated.
[0122] When W2 / W1 was too large and Gv / Gp was too small, the absolute value of my of the soft magnetic alloy powder became too large. As a result, the mY of the magnetic core (toroidal core) made using the soft magnetic alloy powder fell outside the predetermined range, and the DC superposition characteristics deteriorated.
[0123] (Experimental Example 3) Experiment 3 was conducted under the same conditions as Experiment 1, except that the composition of the soft magnetic alloy powder was changed by weight ratio to 64.5Fe-29.2Co-2.4B-1.7Si-1.2P-1.0Cr (Table 5), 64.3Fe-29.1Co-2.4B-1.7Si-1.2P-1.0Cr-0.2C (Table 6), 86.8Fe-11.0Si-2.2B (Table 7), 87.3Fe-7.0Si-2.5Cr-2.5B-0.7C (Table 8), and 94.6Fe-2.0Si-3.0B-0.4C (Table 9), and that no heat treatment was performed on the soft magnetic alloy powder. Experiment 3 was conducted under the same conditions as Experiment 1. In Experiment 3, it was confirmed that all powders consisted of amorphous material.
[0124] [Table 5]
[0125] [Table 6]
[0126] [Table 7]
[0127] [Table 8]
[0128] [Table 9]
[0129] Tables 5 to 9 show that when W2 / W1 and Gv / Gp were suitably controlled, the my and mz values of the soft magnetic alloy powder fell within the predetermined range. Furthermore, the mY and mZ values of the magnetic core (toroidal core) fabricated using the said soft magnetic alloy powder fell within the predetermined range, resulting in good DC superposition characteristics.
[0130] Conversely, when W2 / W1 was too small and Gv / Gp was too large, the absolute value of mz of the soft magnetic alloy powder became too large. As a result, the mZ of the magnetic core (toroidal core) made using the soft magnetic alloy powder fell outside the predetermined range, and the DC superposition characteristics deteriorated.
[0131] When W2 / W1 was too large and Gv / Gp was too small, the absolute value of my of the soft magnetic alloy powder became too large. As a result, the mY of the magnetic core (toroidal core) made using the soft magnetic alloy powder fell outside the predetermined range, and the DC superposition characteristics deteriorated.
[0132] (Experimental Example 4) The composition of the soft magnetic alloy powders by weight is as follows: 97.0Fe-3.0Si (Table 10), 95.5Fe-4.5Si (Table 11), 93.5Fe-6.5Si (Table 12), 84.2Fe-9.3Co-6.5Si (Table 13), 83.3Fe-9.2Co-6.5Si-1.0Cr (Table 14), 55.0Fe-45.0Ni (Table 15), 16.0Fe-79.0Ni-5.0Mo (Table 16), 93.5Fe The experiment was conducted under the same conditions as Experimental Example 1, except for the changes made to the following powders: -4.5Si-2.0Cr (Table 17), 85.5Fe-4.5Si-10.0Cr (Table 18), 85.0Fe-9.5Si-5.5Al (Table 19), 87.4Fe-6.2Si-5.4Al-1.0Ni (Table 20), and 49.0Fe-44.0Ni-2.0Si-5.0Co (Table 21), and the fact that the soft magnetic alloy powder was not heat-treated. Experimental Example 4 was conducted under the same conditions as Experimental Example 1. In Experimental Example 4, it was confirmed that all powders consisted of crystals.
[0133] [Table 10]
[0134] [Table 11]
[0135] [Table 12]
[0136] [Table 13]
[0137] [Table 14]
[0138] [Table 15]
[0139] [Table 16]
[0140] [Table 17]
[0141] [Table 18]
[0142] [Table 19]
[0143] [Table 20]
[0144] [Table 21]
[0145] Tables 10 to 21 show that when W2 / W1 and Gv / Gp were suitably controlled, the my and mz values of the soft magnetic alloy powder fell within the predetermined range. Furthermore, the mY and mZ values of the magnetic core (toroidal core) fabricated using the said soft magnetic alloy powder fell within the predetermined range, resulting in good DC superposition characteristics.
[0146] Conversely, when W2 / W1 was too small and Gv / Gp was too large, the absolute value of mz of the soft magnetic alloy powder became too large. As a result, the mZ of the magnetic core (toroidal core) made using the soft magnetic alloy powder fell outside the predetermined range, and the DC superposition characteristics deteriorated.
[0147] When W2 / W1 was too large and Gv / Gp was too small, the absolute value of my of the soft magnetic alloy powder became too large. As a result, the mY of the magnetic core (toroidal core) made using the soft magnetic alloy powder fell outside the predetermined range, and the DC superposition characteristics deteriorated.
[0148] (Experimental Example 5) Using soft magnetic alloy powders with sample numbers 1, 7, and 11 from Experimental Example 1, the molding pressure was varied. ratio Magnetic cores with varying magnetic permeability μ were fabricated. Similar to Experimental Example 1, the average particle size D2, average circularity C2, mY, mZ, μ, and μHdc of each magnetic core were measured. ratio For the case where the magnetic permeability μ is the same, the increase rate of μHdc of magnetic cores using soft magnetic alloy powders of sample numbers 7 and 11 compared to magnetic cores using soft magnetic alloy powders of sample number 1 was calculated. The results are shown in the table. 22 This will be shown.
[0149] [Table 22]
[0150] Table 22 shows that even when μ is varied, the same trend is observed as when μ = 30. [Explanation of Symbols]
[0151] 10. Elliptical water flow atomizer 60 ... Molten metal supply section 61… Molten metal 61a ... Dropping molten metal 62 … Container 63 … (molten metal) discharge port 64… Heating coil 66… Gas injection nozzle 67 … Injection port 30 … Cooling section 32 … Cylindrical body 33 … Inner peripheral surface 34 … Discharge section 36 ... Coolant outlet 37… Supply line 52 … Coolant discharge port 50 … Coolant layer
Claims
1. A soft magnetic alloy powder comprising: first particles consisting of soft magnetic alloy particles with a particle diameter of D50 or less; second particles consisting of soft magnetic alloy particles with a particle diameter greater than D50 and D60 or less; third particles consisting of soft magnetic alloy particles with a particle diameter greater than D60 and D70 or less; fourth particles consisting of soft magnetic alloy particles with a particle diameter greater than D70 and D80 or less; and fifth particles consisting of soft magnetic alloy particles with a particle diameter greater than D80 and D90 or less. Of the first to fifth particles, the average particle diameter of the nth particle is x n (μm), the average circularity of the nth particle is y n The dispersion of the circularity of the nth particle is z n as, Point (x n , y n When plotting (n=1 to 5) on the xy-plane, the slope my of the approximation line is between -0.0030 and 0.0000. Point (x n , z n A soft magnetic alloy powder in which the slope mz of the approximate line when plotting (n=1 to 5) on the xz plane is 0.00050 or less.
2. The soft magnetic alloy powder according to Claim 1, wherein the mz is 0.00005 or more and 0.00050 or less.
3. A magnetic core comprising: a first particle made of soft magnetic alloy particles with a particle diameter of D50 or less; a second particle made of soft magnetic alloy particles with a particle diameter greater than D50 and D60 or less; a third particle made of soft magnetic alloy particles with a particle diameter greater than D60 and D70 or less; a fourth particle made of soft magnetic alloy particles with a particle diameter greater than D70 and D80 or less; and a fifth particle made of soft magnetic alloy particles with a particle diameter greater than D80 and D90 or less. Let X be the average particle diameter of the n-th particle among the first to fifth particles n (μm), and Y be the average circularity of the n-th particle n , and Z be the variance of the circularity of the n-th particle n , where Point (X n , Y n When plotting (n=1 to 5) on the XY plane, the slope mY of the approximate line is between -0.0030 and 0.0000. Point (X n , Z n A magnetic core in which the slope mZ of the approximate line when plotting (n=1 to 5) on the XZ plane is 0.00050 or less.
4. The magnetic core according to claim 3, wherein the mZ is 0.00005 or more and 0.00050 or less.
5. The magnetic core according to claim 3, further comprising a resin.
6. A magnetic component comprising a magnetic core according to any one of claims 3 to 5.
7. An electronic device comprising a magnetic core according to any one of claims 3 to 5.
Citation Information
Patent Citations
Coated iron based powder for powder magnetic core, and powder magnetic core
JP2006283166A
Soft magnetic material, powder magnetic core, manufacturing method of soft magnetic material, and manufacturing method of powder magnetic core
JP2009070914A
Amorphous soft magnetic powder, toroidal core, inductor and choke coil
JP2011023673A
Dust core
JP2019021906A
Core, reactor, manufacturing method of the core, and manufacturing method of the reactor
JP2019216199A